2019
DOI: 10.33151/ajp.16.686
|View full text |Cite
|
Sign up to set email alerts
|

Care of the Patient with Invasive Meningococcal Disease by Emergency Medical Service Clinicians: A Scoping Review Protocol

Abstract: BackgroundInvasive meningococcal disease (IMD) is a rare but potentially fatal disease. It can rapidly progress within minutes to hours and carries a significant burden of disease worldwide. The role of emergency medical service (EMS) clinicians in providing early care for the patient with IMD is important, but the literature regarding the pre-hospital phase of care is sparse.AimThe aim of this scoping review is to systematically map the literature to identify the scope, depth and key concepts in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…An a priori protocol for this review was published in a peer-reviewed journal 2. The protocol manuscript was prepared in accordance with the PRISMA-Protocols reporting guideline 15.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An a priori protocol for this review was published in a peer-reviewed journal 2. The protocol manuscript was prepared in accordance with the PRISMA-Protocols reporting guideline 15.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the fulminant nature of IMD, it is important that early identification and appropriate management are provided by emergency medical service (EMS) clinicians to reduce morbidity and mortality, and ensure the best patient outcomes. A comprehensive background and rationale for this review can be found in the published review protocol 2…”
Section: Introductionmentioning
confidence: 99%